Induction chemotherapy with paclitaxel and cisplatin followed by radiotherapy for larynx organ preservation in advanced laryngeal and hypopharyngeal cancer offers moderate late toxicity outcome (DeLOS-I-trial) - Dietz, Andreas; Rudat, Volker; Dreyhaupt, Jens; Pritsch, Maria; Hoppe, Florian; Hagen, Rudolph; Pfreundner, Leo; Schröder, Ursula; Eckel, Hans Edmund; Hess, Markus M.; Schröder, Michael; Schneider, Petra; et al. (European archives of oto-rhino-laryngology and head & neck, 2009)
Induction chemo - Larynx - Hypopharynx cancer - Organ preservation - Head and neck